ANALISIS PENGARUH PERSPEKTIF MENTAL PICTURE TERHADAP KEMAMPUAN PRAKTEK SISWA APPROACH PROCEDURAL DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Alfathan Jody M.K; Rany Adiliawijaya P; Bambang Sutarwita (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
The purpose of this research gave a picture about a problem in cadets practice in how to controlled aircraft at approach control procedural laboratory with one of the aspect effect is mental picture perspective. Research method used is quantitative method. Research instruments used is questioner and interview to get the data from each cadets about perspective mental picture and the data of ability of each cadets form the grade of approach control procedural examination. The conclusion is mental perspective has effect to the ability of the cadets practice. One of enhancement support in controlled airspace approach control procedural laboratory is mental picture perspective in everyone cadets must be increase